Orani : my father's village - Nivola, Claire A. (Frances Foster Books/Farrar Straus Giroux, 2011)
Children's book author Claire A. Nivola explores the village of Orani, the tiny hamlet in the mountains of central Sardinia where her father lived before moving to New York during World War II.